Immune Cell-Derived Extracellular Vesicles in the Face of Pathogenic Infections - Keshtkar, Somayeh; Soleimanian, Saeede; Kaviani, Maryam; Sarvestani, Fatemeh Sabet; Azarpira, Negar; Asvar, Zahra; Pakbaz, Sara (Frontiers in Immunology, 2022)
Extracellular Vesicles (EVs) are a collection of vesicles released from cells that play an important role in intercellular communication. Microbial infections are known as one of the major problems in the medical field. Considering the increasing resistance of strains to routine drug treatments, the need for new therapies seems to be more than ever. Recent studies have shown that the EVs released from immune cells during microbial infections had anti-microbial effects or were able to induce neighbouring cells to display anti-microbial effects. This mini-review aimed to explore the latest studies on immune cell-derived EVs in viral, bacterial, fungal, and parasitic infections. Review of the literature demonstrated that specific cargos in EVs were involved in the fight against pathogenic infections. Additionally, the transport of appropriate bioactive molecules including miRNAs, mRNAs, and proteins via EVs could mediate the anti-microbial process. Thus, it could be a proof-of-principle that therapeutic approaches based on EVs derived from immune cells could offer a promising path forward, which is still in early stages and needs further assessments.